KEBHINEKATUNGGALIKAAN DAN PANCASILA SEBAGAI PEMBENTUK KARAKTER PESERTA DIDIK MELALUI BUDAYA SEKOLAH - Jannah, Miftahul; Rahmi Susanti; Meilinda (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2024)
Diversity and Pancasila have noble values ​​that are important in shaping the character of Indonesia's young generation. Strengthening the Pancasila Student Profile in protecting students' character is one of the government's strategies to prevent radicalism. The results of the discussion in this article are that students at SMA Negeri 1 Palembang have implemented diversity in diversity and an appreciation of Pancasila values. Diversity in diversity can be seen in students at school being friends with everyone regardless of differences such as skin colour, gender, ethnicity and language. This can be seen when students can communicate and play well with their peers. The application of character values ​​through school culture can be done through several activities, including; 5S activities (Smiles, Greetings, Accost, Politeness and Courteous); tadarus culture; a culture of reading prayers when starting and ending learning; discipline; and clean culture; honest culture; big day commemoration; dress neatly, and so on.